The Impact of Sweden and Finland’s NATO Membership on Nordic Defence Cooperation - Hálková, Viktorie; Rolenc, Jan Martin, 1980-; Hennlichová, Marcela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The security environment in the Nordic region has gradually worsened since 2014 and was further changed by the war in Ukraine in 2022. Consequently, Finland and Sweden joined NATO in 2023 and 2024, marking the first time all Nordic countries are united in a military alliance. This thesis aims to analyse how the Nordic defence cooperation has evolved following the Sweden and Finland´s accession to NATO, with particular attention to developments in logistics, interoperability and policy coordination. The analysis uses a case study as its methodology and examines key developments in logistics, interoperability and policy coordination through the lens of Regional Security Complex Theory (RSCT), which offers a perspective for understanding security dynamics at a regional level. Overall, the analysis indicates that NATO membership is the key factor in deepening Nordic defence cooperation and highlights significant shifts in the region´s security dynamics following Sweden and Finland´s accession to the Alliance.
Vedoucí práce: Jan Martin Rolenc
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses